Influence of load and temperature on the dry sliding wear behavior of aluminium-Ni3Al composites - Demirel, Mehtap; Muratoglu, Mehtap (Natl Inst Science Communication-Niscair, 2011)
The suitability of Ni3Al intermetallics as reinforcements for Al-base materials for tribological application has been investigated. For this purpose, an Al/Ni3Al (5 wt%, 10 wt% and 15 wt%) composite is prepared by powder metallurgy techniques and tested on a pin-on-ring apparatus. The effects of the applied load (83-150 N) and temperature (25-150 degrees C) at a constant sliding velocity of 0.4 m/s on the wear behavior of Al-Ni3Al composites and wear mechanisms during dry sliding are investigated. The worn surfaces are examined by scanning electron microscopy (SEM) and energy dispersive spectrometry (EDS). It is found that the wear resistance of Al-Ni3Al composites decreased with increasing load and with an increasing fraction of reinforcement Ni3Al particles. With an increasing fraction of Ni3Al particles, the wear resistance of the composites increased at higher test temperatures, but not at lower test temperatures, and generally with increasing test temperatures, the weight loss of composite materials increased slightly. It is also observed that a significant amount of Fe-rich oxide particles become incorporated into the Al matrix during wear, forming a tribolayer.
Keywords: Metal matrix composites; Intermetallics; Tribology; Electron microscopy